Synthesis and Bioassay of Novel Phenylhydrazine and 2,4-Dinitrophenylhydrazine Substituted Carbazoles - Hamid, Almas; Sadiq, Zubi; Yaqub, Ghazala; Khan, Nikhat; Iqbal, Saira; Iqbal, Kashaf; Ijaz, Zainab; Bajwa, Anum (Asian Journal of Chemistry, 2013)
The efficient and rapid synthesis of phenylhydrazine and 2,4-dinitrophenylhydrazine substituted carbazole derivatives is reported using both strategies; conventional and microwave. Both newly prepared compounds shares the same acidic media. Microwave irradiations demonstrated much suitable results with respect to every aspect. Antibacterial and antifungal potential of both compounds were evaluated in terms of minimum inhibitory concentration against Escherichia coli, Staphylococcus aureus, Pasteurella multocida, Bacillus subtilis, Aspergillus flavus, Aspergillus niger, Alternaria solani and Rhizoctonia solani.